Correlation between antimicrobial resistant Propionibacterium acnes and severity of acne vulgaris: Findings from a tertiary hospital - Maria Mayfinna Gozali; Yuli Kurniawati; Mutia Devi; Erial Bahar; Lisa Dewi; Yulia Farida Yahya; Rusmawardiana; Sarah Diba Zulkarnain; Soenarto Kartowigno (Wolters Kluwer Medknow Publications, 2023)
The study of antimicrobial-resistant Propionibacterium acnes was not conducted regularly, especially in Indonesia. Conversely, regular monitoring of antibiotic efficacy through in vitro testing to assess the evolution of current resistance patterns is obligated; thus, filling the gap caused by a lack of appropriate antibiotic surveillance is required. Analyse the correlation between resistance patterns of P. acnes to doxycycline, clindamycin, erythromycin and azithromycin with the severity of acne vulgaris. This is an analytic observational laboratory study with a cross-sectional design of mild to severe acne vulgaris (AV) patients. Specimens were obtained from comedones of 71 patients, which were cultured and identified using biochemical examination. Antimicrobial resistance (doxycycline, clindamycin, erythromycin and azithromycin) to P. acnes was tested by disc diffusion method. Among 71 samples collected, 40 (56.3%) P. acnes isolates were cultured and identified. The incidence of P. acnes resistance to more than one antimicrobial was 45%. Antimicrobial resistances were clindamycin 42.5%, erythromycin 40%, azithromycin 23.5% and doxycycline 12.5%, respectively. According to the contingency coefficient test, there was moderate correlation between the resistance pattern of P. acnes to clindamycin (r = 0.485, P = <0.001) and doxycycline (r = 0.433, P = 0.002) and AV severity. There was weak correlation between the resistance pattern of P. acnes to erythromycin (r = 0.333; P = 0.025) and azithromycin (r = 0.321; P = 0.032) and AV severity. In conclusion, there is a correlation between the pattern of P. acnes resistance to doxycycline, clindamycin, erythromycin, azithromycin and severity of AV.